Visually estimated coronary artery calcium score improves SPECT-MPI risk stratification. (August 2021) - Trpkov, Cvetan; Savtchenko, Alexei; Liang, Zhiying; Feng, Patrick; Southern, Danielle A.; Wilton, Stephen B.; James, Matthew T.; Feil, Erin; Mylonas, Ilias; Miller, Robert J.H.
Highlights: Visually estimated coronary artery calcium was an independent predictor of MACE. VECAC provides complementary anatomic information with other SPECT-MPI markers. Physicians should consider routinely evaluating and reporting VECACS. Abstract: Aims: Computed tomographic attenuation correction (CTAC) scans for single photon emission computed tomography myocardial perfusion imaging (SPECT-MPI) may reveal coronary artery calcification. The independent prognostic value of a visually estimated coronary artery calcium score (VECACS) from these low-dose, non-gated scans is not established. Methods & Results: VECACS was evaluated in 4, 720 patients undergoing SPECT-MPI with CTAC using a 4-point scale. Major adverse cardiac events (MACE) were defined as all-cause mortality, acute coronary syndrome, or revascularization > 90 days after SPECT-MPI. Independent associations with MACE were determined with multivariable Cox proportional hazards analyses adjusted for age, sex, past medical history, perfusion findings, and left ventricular ejection fraction. During a median follow up of 2.9 years (interquartile range 1.8 – 4.2), 494 (10.5%) patients experienced MACE. Compared to absent VECACS, patients with increased VECACS were more likely to experience MACE (all log-rank p < 0.001), and findings were similar when stratified by normal or abnormal perfusion. Multivariable analysis showed an increased MACE risk associated with VECACS categories of equivocal (adjusted hazard ratio [HR] 2.54, 95% CI 1.45–4.45, p = 0.001), present (adjusted HR 2.44, 95% CI 1.74–3.42, p < 0.001) and extensive (adjusted HR 3.47, 95% CI 2.41–5.00, p < 0.001) compared to absent. Addition of VECACS to the multivariable model improved risk classification (continuous net reclassification index 0.207, 95% CI 0.131 – 0.310). Conclusion: VECACS was an independent predictor of MACE in this large SPECT-MPI patient cohort. VECACS from CTAC can be used to improve risk stratification with SPECT-MPI without additional radiation.